Hundreds of new DNA barcodes for South African sponges. Issue 7 (3rd October 2021) - Ngwakum, Benedicta B.; Payne, Robyn P.; Teske, Peter R.; Janson, Liesl; Kerwath, Sven E.; Samaai, Toufiek
Abstract : DNA barcoding based on a fragment of the cytochrome c oxidase subunit I (COI) gene from the mitochondrial genome is widely applied in species identification, species discovery and biodiversity studies. The aim of this study was to establish a barcoding reference database of sponges collected from South Africa, and evaluate the applicability of the COI gene for aiding in the identification of sponges in combination with tentative morphological identifications. A total of 317 mitochondrial COI barcode sequences, with an additional 21 extended COI fragments and 24 nuclear ITS sequences, were obtained from 11 orders, 38 families, 58 genera and 124 species of spiculated sponges. A Neighbour Joining (NJ) trees that were reconstructed using these sequences in most cases clustered species in accordance with their current taxonomic identification, and we conclude that COI sequencing can be used to aid in the identification of sponge species. We further demonstrate that DNA barcoding analysis has potential to uncover cryptic sponge species, and to reveal dubious morphological identifications. We recommend that future taxonomic studies of South African sponges incorporate multiple sources of information for species identification or discovery.